On the Stylistic and Cultural Awareness of Chen Yan’s Novels: Taking The Protagonist and The Backstage Clan as Examples - LIU Qiong (Frontiers of literary studies in China, 2023)
The Protagonist is another fulllength masterpiece of realism by Chen Yan following his previous novel The Backstage Clan. His rich experience in drama creation enables Chen Yan to skillfully employ classical literature and traditional opera librettos, and be keener on entering a narrative where novel and opera communicate without any barriers, thereby forming his distinctive narrative aesthetic. In addition, Chen Yan has proficiently created in the abovementioned books typical characters such as Diao Shunzi and Yi Qin’e, creating a blueprint for how these two novels will be passed down to later generations. Unlike The Backstage Clan, which focuses on the extraordinary nature of ordinary people, The Protagonist presents the potential of the rise of ordinary people and a panorama of man and culture by portraying the legendary lives of the protagonist and the secondary protagonist.